The Role of Brand Image in Mediating The Influence of Online Customer Reviews on Purchasing Decisions (Study of Tokopedia Users in Denpasar City) - I Putu Bagus Dharma Surya Nanda; Ni Made Wulandari Kusumadewi (International Journal of Economics, Management and Accounting, 2025)
Marketplace or E-commerce is an internet-based online media as a place to conduct business activities and transactions between buyers and sellers. In the marketplace or e-commerce, buyers can search for as many suppliers as possible with the desired criteria so that they get the appropriate market price. Tokopedia is a marketplace based in Indonesia. The purpose of this study is to explain the role of brand image in mediating the influence of online customer reviews on purchasing decisions. This study was conducted in Denpasar City with a sample of 100 respondents using the non-probability sampling method with the purposive sampling technique. The data analysis technique used is the inferential analysis technique including confirmatory factor analysis (CFA), path analysis, Sobel test and VAF test. The results of this study indicate that online customer reviews have a positive and significant effect on purchasing decisions. Online customer reviews have a positive and significant effect on brand image. Brand image has a positive and significant effect on purchasing decisions. Brand image partially mediates the influence of online customer reviews on purchasing decisions for Tokopedia users in Denpasar City. The implications of this study can be used as consideration and input for Tokopedia in improving consumer purchasing decisions by considering the variables of online customer reviews and brand image.